Trends in bowhead whales in West Greenland: Aerial surveys vs. genetic capture‐recapture analyses. Issue 1 (24th July 2014) - Rekdal, Silje L.; Hansen, Rikke Guldborg; Borchers, David; Bachmann, Lutz; Laidre, Kristin L.; Wiig, Øystein; Nielsen, Nynne Hjort; Fossette, Sabrina; Tervo, Outi; Heide‐Jørgensen, Mads Peter
Abstract We contrast two methods for estimating the trends of bowhead whales (Balaena mysticetus) in West Greenland: (1) double platform visual aerial survey, corrected for missed sightings and the time the whales are available at the surface; and (2) a genetic capture‐recapture approach based on a 14‐yr‐long biopsy sampling program in Disko Bay. The aerial survey covered 39, 000 km2 and resulted in 58 sightings, yielding an abundance estimate of 744 whales (CV = 0.34, 95% CI: 357–1, 461). The genetic method relied on determining sex, mitochondrial haplotypes and genotypes of nine microsatellite markers. Based on samples from a total of 427 individuals, with 11 recaptures from previous years in 2013, this resulted in an estimate of 1, 538 whales (CV = 0.24, 95% CI: 827–2, 249). While the aerial survey is considered a snapshot of the local spring aggregation in Disko Bay, the genetic approach estimates the abundance of the source of this aggregation. As the whales in Disko Bay primarily are adult females that do not visit the bay annually, the genetic method would presumably yield higher estimates. The studies indicate that an increase in abundance observed between 1998 and 2006 has leveled off.